Peran Work-Life Balance Sebagai Variabel Mediasi dalam Pangaruh Media Sosial, Beban Kerja dan Burnout terhadap Kinerja Karyawan Generasi Z - Jamhur Mursidan Rais; Ahmad Mardalis (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study is to evaluate the role of work-life balance as a mediator in the influence of social media, workload, and burnout on the performance of Generation Z employees. The methodology applied is quantitative, with data collection from 170 participants through questionnaires. Data analysis was conducted using SmartPLS version 3.0. The findings indicate that workload, burnout, and social media have a significant influence on the performance of Generation Z employees. Work-life balance is also shown to play an important role in improving performance, although it does not function as a mediator in the interaction between burnout, workload, and social media. These results indicate that although work-life balance plays an important role, factors such as workload and burnout have a more dominant influence. This study provides important insights for organizations in designing more effective strategies to improve the performance of Generation Z employees by considering relevant factors.